2016
DOI: 10.18632/oncotarget.11258
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of ST6GalNAc-1 expression in patients with non-metastatic clear cell renal cell carcinoma

Abstract: BackgroundSialyltransferase ST6GalNAc-1 is highly expressed in tumor cells and associated with tumor aggressiveness and poor prognosis. In the present study, we aimed to investigate the clinical and prognostic significance of sialyltransferase ST6GalNAc-1 in patients with non-metastatic ccRCC.ResultsHigh expression of ST6GalNAc-1 in tumor tissue was an independent prognostic factor for overall survival (p<0.001) and recurrence free survival (p<0.001) in multivariate analysis. The nomograms could give better pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In recent years, ST6GalNAc-I has been widely recognized for its role in tumor activity by regulating Tn and STn antigens [ 76 ]. Qi Bai et al detected ST6GaNAc-1 high expression in tumors by tissue microarray and immunohistochemical staining and showed that ST6GalNAC-I affected the patient’s overall survival in non-metastatic ccRCC [ 77 ]. Mucins contain a large amount of O-glycosylation, and abnormal expression or glycosylation of mucins can alter the biological behaviors of tumor cells, such as growth, differentiation, adhesion, and invasion [ 78 , 79 ].…”
Section: O-glycansmentioning
confidence: 99%
“…In recent years, ST6GalNAc-I has been widely recognized for its role in tumor activity by regulating Tn and STn antigens [ 76 ]. Qi Bai et al detected ST6GaNAc-1 high expression in tumors by tissue microarray and immunohistochemical staining and showed that ST6GalNAC-I affected the patient’s overall survival in non-metastatic ccRCC [ 77 ]. Mucins contain a large amount of O-glycosylation, and abnormal expression or glycosylation of mucins can alter the biological behaviors of tumor cells, such as growth, differentiation, adhesion, and invasion [ 78 , 79 ].…”
Section: O-glycansmentioning
confidence: 99%
“…Despite of surgery, some of the patients still develop postoperative recurrence or metastasis. [4,5] Metastatic stage represents a challenge for ccRCC patients, due to its high resistance to chemotherapy and radiotherapy. [6,7] Although great progress has been made in the therapeutic strategy, the 5-year survival rates of patients with ccRCC are still not ideal.…”
Section: Introductionmentioning
confidence: 99%
“…HOXC6, a member of the homeobox family that encodes highly conserved transcription factors, not only plays a crucial role in CRC [27], but also functions as an independent prognostic marker for hepatocellular carcinoma [28] and prostate cancer [29]. LINC00261 [30,31,32], TNFRSF11A [33], CASP1 [34], ST6GALNAC1 [35], and PIGR [36] also play prognostic roles in cancer. Only PCSK1’s function in cancer and immunity has not been researched.…”
Section: Discussionmentioning
confidence: 99%